PENGARUH LITERASI KEUANGAN TERHADAP PENGELOLAAN KEUANGAN PRIBADI MAHASISWA - Mahiro Sholeha Niu; Radia Hafid; Rierind Koniyo; Raflin Hinelo; Agil Bahsoan (Universitas Negeri Gorontalo, 2025)
This study aims to examine the effect of financial literacy on the personal financial management of the 2024 cohort of students in the Department of Economic Education, Faculty of Economics and Business, Universitas Negeri Gorontalo. The study employed a quantitative approach using an associative research method. The population consisted of 184 students, with a sample of 65 respondents selected through simple random sampling using the Slovin formula. Data were collected using a Likert-scale questionnaire. Data analysis included validity testing, reliability testing, normality testing, and simple linear regression analysis using SPSS software. The results indicate that financial literacy has a positive and significant effect on students' personal financial management. This is evidenced by a correlation coefficient (r) of 0.781, indicating a strong relationship between the two variables. The coefficient of determination (R²) is 0.610, meaning that 61% of the variation in students' personal financial management is explained by financial literacy, while the remaining 39% is influenced by other factors outside the scope of this study. The hypothesis testing results show that the calculated t-value exceeds the critical t-value (9.930 1.999) at a significance level of α = 5%, with a significance value of 0.000 0.05. Therefore, H₀ is rejected and H₁ is accepted. It can be concluded that the higher the level of students' financial literacy, the better their ability to manage their personal finances.